ANALISIS GERAK DASAR TIGER SPRONG BAGI PESERTA DIDIK DI SMP PGRI PATROL INDRAMAYU - Moh. Daimudin Ulin Nuha; Anang Setiawan; Seni Oktriani; Mochamad Zakky Mubarok (Journal of Physical Activity and Sports (JPAS), 2025)
This study aims to analyse the basic skills of the tiger sprong movement in students of SMP PGRI Patrol Indramayu. Performing this movement requires flexibility and high self-confidence, especially for female students, because they often feel weak and hesitate to perform movements that are considered difficult and risky. The tiger sprong movement is similar to the forward roll, with the main difference starting with both feet, jumping, and floating in the air. Executing the basic tiger sprong movement requires students to master the basic techniques of the forward roll. The difference lies in the need to jump and slide when executing the forward roll in the tiger sprong. This study applies a Descriptive approach with Quantitative Methods. Descriptive Approach with Quantitative Methods is a research method that explains the subject's activities through numerical data that serves as information and reference. The subjects in this study included 120 students from SMP PGRI Patrol Indramayu, including students from grades VII, VIII, and IX. By utilizing the quota sampling method, 20 students of grade VIII were selected as samples according to the characteristics or criteria desired by the researcher. The data collection technique in this study used a test, which is an instrument to assess and measure the achievement of predetermined goals. The assessment criteria for tiger sprong include the continuation of the movement from a forward jump with both feet pushing simultaneously, while both arms are directed forward to support the body when "landing" on the mat, followed by a forward roll. The assessment tool used in this study is an instrument that has been tested on students at SMP Negeri 25 Bandar Lampung. Based on the results of data analysis conducted by the researcher, as many as 2 people or 10% are included in the very good category, 4 people or 20% are classified as good, 7 people or 35% are at a sufficient level, and 7 people or 35% are classified as less. From the results of data analysis and discussion, it can be seen that the level of basic tiger sprong movement ability of students at SMP PGRI Patrol Indramayu is included in the sufficient category.